Obesity and Cancer Risk: Emerging biological mechanisms and perspectives - Avgerinos, KI; Spyrou, N; Mantzoros, C.S.; Dalamaga, M (Metabolism, 2018)
Continuously rising trends in obesity-related malignancies render this disease spectrum a public health priority. Worldwide, the burden of cancer attributable to obesity, expressed as population attributable fraction, is 11.9% in men and 13.1% in women. There is convincing evidence that excess body weight is associated with an increased risk for cancer of at least 13 anatomic sites, including endometrial, esophageal, renal and pancreatic adenocarcinomas; hepatocellular carcinoma; gastric cardia cancer; meningioma; multiple myeloma; colorectal, postmenopausal breast, ovarian, gallbladder and thyroid cancers. We first synopsize current epidemiologic evidence; the obesity paradox in cancer risk and mortality; the role of weight gain and weight loss in the modulation of cancer risk; reliable somatometric indicators for obesity and cancer research; and gender differences in obesity related cancers. We critically summarize emerging biological mechanisms linking obesity to cancer encompassing insulin resistance and abnormalities of the IGF-I system and signaling; sex hormones biosynthesis and pathway; subclinical chronic low-grade inflammation and oxidative stress; alterations in adipokine pathophysiology; factors deriving from ectopic fat deposition; microenvironment and cellular perturbations including vascular perturbations, epithelial-mesenchymal transition, endoplasmic reticulum stress and migrating adipose progenitor cells; disruption of circadian rhythms; dietary nutrients; factors with potential significance such as the altered intestinal microbiome; and mechanic factors in obesity and cancer. Future perspectives regarding prevention, diagnosis and therapeutics are discussed. The aim of this review is to investigate how the interplay of these main potential mechanisms and risk factors, exerts their effects on target tissues provoking them to acquire a cancerous phenotype.